PREVALENCE OF METABOLIC ASSOCIATED FATTY LIVER DISEASES AMONG PATIENTS WITH POLYCYSTIC OVARIAN SYNDROME DURING THEIR SONOGRAPHIC EVALUATION (Journal of Medical & Health Sciences Review, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder. It is frequently associated with metabolic complications, including metabolic-associated fatty liver disease (MAFLD). We aimed to assess the prevalence of MAFLD among women with PCOS during their sonographic evaluation and to explore the relationship between MAFLD and patient characteristics.Methods: We conducted a descriptive cross-sectional study at the Radiology Department of Dr. Ruth K.M. Pfau Civil Hospital and Dow University of Health Sciences over a six-month period. A total of 346 women with PCOS, diagnosed clinically and undergoing abdominal ultrasonography, were included. We collected demographic and clinical data, including age, parity, and duration since PCOS diagnosis, socioeconomic status, and marital status. We diagnosed MAFLD based on sonographic evidence of hepatic steatosis.Results: MAFLD was present in 60.1% of the participants. Women aged 31–45 years had a significantly higher prevalence (77.8%) compared to those aged 18–30 years (51.1%, p=0.01). Longer PCOS duration, higher parity, and middle-income status were also significantly associated with increased MAFLD prevalence. Married and divorced women showed a higher burden of MAFLD compared to their unmarried counterparts. Although place of residence showed a trend toward significance, it did not reach statistical relevance (p=0.06).Conclusion: We identified a high prevalence of MAFLD among women with PCOS, with strong associations across several demographic and clinical variables. These findings underscore the need for targeted metabolic screening and early intervention in this population to mitigate the risk of long-term hepatic and metabolic complications.